Effects of argon CID in MALDI Ms(n) analysis of Peptides and Proteins - Ven, Henrik Cornelisson van der (2009)
In recent years the use of mass spectrometers in protein studies has proven extremely useful. It enables scientists to get analysis of a sequence, the composition of a complex solution or even the 3-D structure of a protein. During matrix-assisted laser desorption/ionization (MALDI –TOF) protein research at the Uni. Iceland Science institute the well known “middle range ion suppression” has caused considerable problems in MALDI –TOF MS/MS analysis of proteins. In an effort to alleviate this shortcoming, we investigated the use of argon collision induced decay (CID) in MS/MS spectra. We compared tryptic digested bovine serum albumin (BSA) MS and MS/MS spectra from selected parent ions using LIFT with or without CID. We observed that the resulting MS/MS spectra were practically superimposable and that there was no conclusive difference between the analysed peptide sequences. For MS/MS spectra, the BSA CID spectra showed improvement in both intensity of the signal and signal to noise ratio. The strikingly similar MS/MS spectra for BSA obtained with CID and without, suggest that collision induced decay does not play a significant role in CID-LIFT experiments. These results lead to speculation on the MALDI laser production of metastable ions and if the ions formed possess such large amounts of internal energy that they are capable of promoting fragmentation processes in the time window corresponding to the flight time between ion source and the acceleration electrode placed after the collision cell.